Placental Findings in Lysosomal Storage Disease Diagnosis: A Case Report of Galactosialidosis - Sasha Libbrecht; Francois Eyskens; Sabine Declercq; Cecile Colpaert (Hindawi Limited, 2020)
Introduction. Lysosomal storage disorders (LSDs) are rare diseases with more than 50 different entities described today. The spectrum of phenotypes varies from severe to lethal and early-onset disease to mild and late onset. Recognition of the clinical signs and diagnostic workup is challenging and requires expertise. Diagnosis relies on finding abnormal metabolites in urine and serum followed by further enzymatic or molecular analysis. Routine histological examination of the foetal and placental tissues frequently shows vacuolisation, providing a readily available important clue to the diagnosis. Case Report. A third child of consanguineal parents showed several dysmorphic features and a complicated neonatal period with eventual demise in the early postneonatal period due to respiratory failure. An LSD was suspected based on clinical presentation, urine metabolite excretion, skeletal radiograph, and vacuolisation in lymphocytes and placental tissues on, respectively, blood smear and routine histological examination. Homozygosity mapping favoured galactosialidosis. The diagnosis was confirmed by massive parallel sequencing, revealing a single nucleotide variation in the CTSA gene (c.265A>C, p.Ser89Arg). Discussion. Histological placental examination may be either the first clue or complimentary evidence in recognizing LSDs. It is important to recognize these clues as it may prompt further investigation and facilitate earlier recognition of the disease.